A Strategy of SOC Estimation and Correction for Vehicle PowerBatteries Based on Double-integrator - WEN Jianfeng; WANG Quan; LIU Yuan; HUANG Hao; ZHONG Xiongwu; XIONG Ziyou (Kongzhi Yu Xinxi Jishu)
It addressed cumulative error and the maximum available capacity variation of the Ampere-hour integral method for power battery SOC(state of charge) estimation under actual operating conditions , analyzed the relationship between different charging and discharging rates, voltage and capacity under different temperature conditions through a large number of tests, and proposed a strategy of SOC estimation and correction based on double-integrator. SOC is calculated in real time with a main integrator in actual operating conditions. When the main integrator has errors, a temporary integrator is used to conditionally correct it. According to the eight correction states of the two correction situations existing in the actual vehicle conditions, the correction strategy is determined. Simulation and test results show the validity of the method, which can effectively decrease cumulative error and improve SOC accuracy